Derivação de células tronco de tecido ovariano na espécie canina - Trindade, Amanda Baracho [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Research with canine stem cells contributes to the progress of veterinary and human cellular therapies, because the dog is often the best animal model for many hereditary and acquired human diseases. While embryonic SC have unlimited differentiation potential (i.e. pluripotent), adult-derived multipotent SC are often preferred for ease of recovery from the patient itself (i.e. autologous) and for avoiding ethical constraints of destroying embryos to obtain pluripotent SC. Recent promising studies have shown the existence SC in ovarian tissue, that have greater proliferative and differentiation potential than SC in other adult tissues. Based on this evidence, the aim of this project was to obtain stem cells isolated from ovarian tissue of adult dogs. In experiment I, we evaluated morphological and kinetic properties of collagenase-digested ovarian and adipose derived SC. Adipose derived cells yielded more cells per tissue after 72h in culture (1937 ± 592.6 vs 1771 ± 262.1), both cells had the same fibroblastic morphology. The growth curve showed that adipose derived cells started the exponential growth before the ovarian derived cells, however when the both were multiplying, the population doubling time was the same. All the derived cells types were able to form colonies, however, adipose derived cells formed more colonies than ovarian derived cells (37.08 ± 2.10 vs. 27.08 ± 1.45). Experiment II aimed at characterizing at the molecular level the SC obtained in experiment I. We evaluated the expression of mesenchymal and pluripotent markers through immunofluorescence (flow cytometry and confocal microscopy) and PCR. Both cells from expressed CD90, CD44, CD194 and CD 105 by PCR, were positive for CD44, CD90 (only the adipose tissue) and negative for CD45 and CD34 by immunocytochemistry analysis. By flow cytometry, 37.08%+-11.35% of the population of cells derived from ovarian tissue was positive for CD90, while 62.05%+-8.40% of ...

O estudo de células tronco em cães corrobora com o progresso das terapias celulares, tanto veterinárias quanto humanas, uma vez que a espécie canina é um modelo de estudo para desenvolvimento de doenças humanas hereditárias e, também, adquiridas. As CT multipotentes derivadas de tecido são geralmente as mais utilizadas, sobretudo pela facilidade de obtenção por meio do próprio animal (autólogas) e por não envolverem questões éticas, as quais limitam o uso das células tronco embrionárias. Estudos recentes e promissores demonstraram a existência de CT no ovário, com grande capacidade de proliferação e possível capacidade pluripotente. Com base nessas evidências, este projeto propôs a obtenção de células tronco isoladas a partir do tecido ovariano de cães adultos, utilizando o tecido adiposo como controle. Para tanto, foram delineados três experimentos: o experimento I possuía o objetivo de verificar as características de crescimento e morfológicas. Então, foi realizado o isolamento de células provenientes do tecido ovariano e adiposo, após digestão em colagenase, Após 3h do inicio do cultivo, foi realizada a primeira troca de meio para seleção de células aderentes ao plástico. Após 72h de cultivo primário, o tecido adiposo possuía mais células por grama de tecido em relação ao ovariano (1937 ± 592,6 vs 1771 ± 262,1), ambas as células derivadas apresentaram morfologia fibroblástica. Em relação às análises de crescimento, o tempo de duplicação da população foi similar em ambos os tipos celulares. Tanto as células do tecido adiposo, como as do ovariano foram capazes de formar colônias, entretanto as do tecido adiposo mostraram uma maior capacidade de formar colônias que as células do tecido ovariano (37,08 ± 2,10 vs. 27,08 ± 1,45, p<0,05). O experimento II possuía o objetivo de realizar a caracterização molecular das células obtidas no experimento I. Tanto as células do...
Keywords: Cão; Células-tronco; Ovarios; Tecido adiposo; Marcadores biologicos; Citometria de fluxo; Stem cells